1994
DOI: 10.1111/j.1365-2265.1994.tb02535.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the prevalence of clear‐cut endocrine disorders and polycystic ovaries in 350 patients presenting with hirsutism or androgenic alopecia

Abstract: For the exclusion of enzyme deficiencies and virilizing tumours clinical assessment and a single serum testosterone measurement will suffice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1
9

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(76 citation statements)
references
References 24 publications
5
61
1
9
Order By: Relevance
“…Specifically, ovarian ultrasound was not routinely used in the diagnosis of PCOS. O'Driscoll and co-workers (8) studied 350 women with 'hirsutism or androgenetic alopecia' (the study does not specify how many women had alopecia and how many had hirsutism) and found a 60% prevalence of PCO upon ultrasound scan (8). They did not report on androgen levels apart from describing eight patients with clearcut endocrine disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, ovarian ultrasound was not routinely used in the diagnosis of PCOS. O'Driscoll and co-workers (8) studied 350 women with 'hirsutism or androgenetic alopecia' (the study does not specify how many women had alopecia and how many had hirsutism) and found a 60% prevalence of PCO upon ultrasound scan (8). They did not report on androgen levels apart from describing eight patients with clearcut endocrine disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The etiologies of hirsutism in this study were PCOS (79%), IH (13%), IHA (6%), and NCAH (2%), which was similar to the previous literature (26,35,36,37,38). Patients were checked for the presence of ovulation, and hirsute patients with anovulatory regular cycles were included in the PCOS group.…”
Section: Discussionmentioning
confidence: 57%
“…Women with OH typically present with a long history of slowly progressive hyperandrogenism often resulting in virilization. Their hormonal profile is characterized by markedly increased serum testosterone levels (O150 ng/dl) in the absence of other elevated androgens, accompanied with high gonadotropin levels (39,40,41); ultrasound examination usually reveals bilaterally bigger than normal postmenopausal ovaries (mean size 7.7G2.3 vs 2.3G0.01 ml respectively) (39,42,43). The diagnosis is confirmed histologically demonstrating the characteristic nests of differentiated ovarian interstitial cells into steroidogenically active luteinized stromal cells throughout the ovarian stroma (44).…”
Section: Ovarian Hyperthecosismentioning
confidence: 82%